Penurunan Kecemasan Ibu Nifas Menggunakan Totok Wajah Di Fasilitas Pelayanan Persalinan - Sumantri Sumantri; Dewi Susilowati; Dian Kurnia Wati (Jurnal Kebidanan dan Kesehatan Tradisional, 2016)
Abstract: Full-Blooded Face, Anxiety, Mother Postpartum. Post partum (puerperal) is the future return of the reproductive organs such as the state before becoming pregnant within six weeks after delivery. One of the psychological disorders suffered postpartum mothers is anxiety. Blooded face is a complementary therapy to reduce stress and anxiety. The aim of research to determine the effect on reducing anxiety blooded face puerperal women in childbirth care facility in Wonogiri districts. This study uses a pre-experimental design with one group pretest posttest design. Population in this research is the post partum mothers who gave birth and postpartum controls in BPM Siti Syamsiyah Wonogiri and RB. Nur Annisa Wonogiri in March-May 2014. The sampling technique using purposive sampling. Data were analyzed using the Wilcoxon test. Assessment of anxiety 30 minutes before full blooded face the majority of mild anxiety, as many as 23 respondents (58.97%). Assessment of anxiety 24 hours after the majority of full-blooded face no anxiety as much as 33 respondents (84.61%). Blooded face significantly influence the decrease in anxiety scores. ρ = 0.00 (ρ <0.05); x = 16.20 to 8.46. The magnitude of the effect of ± 7.74. There is a full-blooded face effect on reducing anxiety postpartum mothers. Recommendations for delivery care facilities to be able to apply blooded face for postpartum mothers.